Heavy metal blood levels and their age-dependent changes in patients undergoing hemodialysis at Jordan Islamic Hospital - Abu Orabi, Faten M.; Fawzi, Mohammad; Humaidi , Jamal; Shammout, Mohammad-Jamal; Saleh, Rawand; Hakawati , Hedaya; Abu-Rayyan, Ahmed (Ukrainian Journal of Nephrology and Dialysis, 2024)
End-stage kidney disease (ESKD) is increasingly recognized as a major global health issue. Heavy metal exposure is a significant risk factor for ESKD. The present study aimed to assess the blood levels of cadmium (Cd), lead (Pb), copper (Cu), and zinc (Zn), and to investigate their variations with age among patients undergoing hemodialysis (HD). Methods. A cross-sectional study was conducted in Amman, Jordan, from January to December 2023. The study included 80 ESKD patients undergoing hemodialysis and 80 healthy controls, both groups aged 20-60 years, divided into four age ranges: 20-29, 30-39, 40-49, and 50-60 years. Blood samples were analyzed for Pb, Zn, Cd, and Cu using atomic absorption spectrometry. Data were analyzed using ANOVA, and p-values <0.05 were considered significant. Results. The concentrations of Pb, Cd, and Cu were significantly higher in ESKD patients compared to healthy controls, while Zn levels were notably lower in ESKD patients. Specifically, Pb levels averaged 27.65 µg/dL in ESKD patients versus 1.06 µg/dL in controls (p = 0.006). Cd levels averaged 1.035 µg/dL in ESKD patients versus 0.0485 µg/dL in controls (p = 0.008). Cu levels averaged 270.1 µg/dL in ESKD patients versus 81.8 µg/dL in controls (p = 0.004). Zn levels were significantly reduced in ESKD patients, averaging 29.5 µg/dL compared to 82.45 µg/dL in controls (p = 0.035). Age-dependent variations showed that Pb (p = 0.01 ), Cd (p = 0.043), Cu (p = 0.01), and Zn (p = 0.037 ) levels increase with age in ESKD patients, suggesting age-related differences in metal accumulation and metabolism. Conclusion: This study highlights significantly elevated levels of Pb, Cd, and Cu, and reduced Zn levels in ESKD patients undergoing hemodialysis compared to healthy controls. Age-dependent differences in metal concentrations suggest that the accumulation and metabolism of these metals may be influenced by age in ESKD patients. These findings underscore the need for further research into the impact of environmental toxins on kidney health.